(untitled) (American International Journal of Economics and Finance Research, 2022)
The Covid-19 global pandemic has affected most companies financially as it has led to massive uncertainties across all sectors and industries. In such situation it requires the refined, and highly integrated accounting information to measure and reflect the economic operation situation and provide early warning to decision makers. The study uses online empirical recourses by the name of Covid-19 pandemic impact on the industries and accounting measurement of the business industries in different online database sources such as Google Scholars, Springer Link, Wiley, Science Direct, JSTOR, Emerald full text, Scopus, and EBSCO HOST. The review findings show that there are different accounting measurement used to measure the impact of Covid-19 on various business industries. The findings of the study also identified that different industries react differently to Covid-19, thus the study findings could be used to draw policy guideline for the industries which were significantly affected by the epidemic. JEL Classification Codes: H83, O14.